Airflow Patterns in Double-Occupancy Patient Rooms May Contribute to Roommate-to-Roommate Transmission of Severe Acute Respiratory Syndrome Coronavirus 2. (27th April 2022) - Cadnum, Jennifer L; Jencson, Annette L; Alhmidi, Heba; Zabarsky, Trina F; Donskey, Curtis J
Abstract: Background: Hospitalized patients are at risk to acquire severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from roommates with unrecognized coronavirus disease 2019 (COVID-19). We hypothesized that airflow patterns might contribute to SARS-CoV-2 transmission in double-occupancy patient rooms. Methods: A device emitting condensed moisture was used to identify airflow patterns in double-occupancy patient rooms. Simulations were conducted to assess transfer of fluorescent microspheres, 5% sodium chloride aerosol, and aerosolized bacteriophage MS2 between patient beds 3 meters apart and to assess the effectiveness of privacy curtains and portable air cleaners in reducing transfer. Results: Air flowed from inlet vents in the center of the room to an outlet vent near the door, resulting in air currents flowing toward the bed adjacent to the outlet vent. Fluorescent microspheres (212–250-µm diameter), 5% sodium chloride aerosol, and aerosolized bacteriophage MS2 released from the inner bed were carried on air currents toward the bed adjacent to the outlet vent. Closing curtains between the patient beds reduced transfer of each of the particles. Operation of a portable air cleaner reduced aerosol transfer to the bed adjacent to the outlet vent but did not offer a benefit over closing the curtains alone, and in some situations, resulted in an increase in aerosol exposure. Conclusions: Airflow patterns in double-occupancy patient rooms may contribute to risk for transmission of SARS-CoV-2 between roommates. Keeping curtains closed between beds may be beneficial in reducing risk. Abstract : Hospitalized patients can acquire severe acute respiratory syndrome coronavirus 2 from infected roommates. Using simulations, we demonstrated that airflow patterns in double-occupancy rooms can facilitate exposure to aerosol particles. Closing curtains between beds may reduce the risk for transmission.